Optimalisasi Pemanfaatan Absensi Digital untuk Modernisasi Layanan Administrasi Pemerintahan Desa - Nuraisyah, Nuraisyah; Hastomo, Widi (JPM: Jurnal Pengabdian Masyarakat, 2026)
This community service activity was conducted in Suka Damai Village to improve the quality of village administrative services through participatory mentoring in the implementation of a digital attendance system. The main problems faced by the partner included the use of manual attendance records, low administrative efficiency, a high risk of recording errors, and limited digital literacy among village officials. This program aimed to enhance the capacity and independence of village officials in managing attendance administration in an orderly, accurate, and transparent manner. The service implementation employed a participatory mentoring approach that actively involved village officials through needs analysis, system usage training, intensive mentoring, as well as monitoring and evaluation stages. The results indicate positive changes among the partners, reflected in increased understanding of information technology, reduced reliance on manual attendance records, and improved independence of village officials in managing the digital attendance system sustainably. Furthermore, the attendance administration process became more structured, accessible, and supportive of transparent village governance. This community service program provides a practical contribution to empowering village officials and has the potential to be replicated in other villages facing similar administrative challenges.